PEMBERDAYAAN MASYARAKAT ISLAM MELALUI PEMANFAATAN HUTAN KEMASYARAKATAN DALAM MENINGKATKAN PENDAPATAN EKONOMI DI DESA MEKAR JAYA KECAMATAN GEDUNG SURIAN KABUPATEN LAMPUNG BARAT - Sumarni, Sumarni; Ghazali, M. Bahri; Wiranto, Bambang Budi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2022)
Community forest management is one of the land management strategies that can support household food availability because this program provides opportunities for local communities to take advantage of protected forest lands. The Wana Jaya Farmers Group Association (Gapoktan) is divided into two sub-groups, namely the Forest Farmers Group (KTH) I and the Forest Farmers Group (KTH) II. Community Forest Management (HKm). This study aims to describe the process and success of the efforts made by Gapoktan Wana Jaya in increasing the economic income of the community. This study uses a qualitative approach, taking the background in the Wana Jaya Gapoktan located in Mekar Jaya Village. The subject of this research is the Joint Farmers Group (Gapoktan) of Wana Jaya which is divided into two sub groups, namely the Forest Farmers Group (KTH) I and the Forest Farmers Group (KTH) II using the Purposive Sampling so that there are criteria in determining the sample. Based on the results of research with activities carried out by the Wana Jaya Gapoktan that resulted in an increase in the community's economy, the results obtained by the community did not always increase, not infrequently they experienced a decrease in crop yields so that it greatly affected income. The recommendation of this research is addressed to the farmer groups so that they continue to develop their capabilities in the use of community forests.